Psychotherapy in schizophrenia: a retrospective controlled study. Issue 2 (3rd April 2018) - Haram, Annbjørg; Jonsbu, Egil; Fosse, Roar; Skårderud, Finn; Hole, Torstein
ABSTRACT: Introduction: Although pharmacological interventions have been the mainstay of treatment for schizophrenia, there has been a growing recognition of the importance of psychotherapy. Aims: To investigate whether a novel psychotherapeutic approach, dialog therapy (DT), has an effect beyond standard psychiatric treatment (ST) in schizophrenia. Methods: Twenty-four patients diagnosed with schizophrenia and treated with DT and 24 patients matched on age, sex, and diagnosis receiving ST were included in the study. Results: At follow-up after a mean of 4 years and 1 month, the DT group had significantly higher scores on the GAF functions (GAF-F) and GAF symptoms (GAF-S) subscales compared to the ST group. Effect sizes (Cohen's d) were very large, 238 for GAF-S and 241 for GAF-F. The number and doses of psychoactive drugs were significantly lower in the DT group compared to the ST group at follow-up, despite a shorter time in psychotherapy in the DT group. Conclusions: This study provides preliminary evidence that dialog therapy may lead to improvements in symptoms and functioning compared to standard psychiatric treatment.